Subjective beliefs and schooling decisions - Christian Belzil (Institute for the Study of Labor (IZA), 2007)
This paper considers the estimation of sequential schooling decisions made by agents who are endowed with subjective beliefs about their own ability. I use unique Italian panel data which provide information on i) the curvature of the per-period utility function, ii) schooling decisions, iii) post-schooling earnings, in order to estimate the future component of the differences in intertemporal utilities of school and work independently from the present component, (as in Geweke and Keane, 1995, 2001), and evaluate the importance of present bias. Under certain conditions, which include imposing equality between the modal belief and true ability, I recover individual specific subjective probability distributions. I estimate both the degree of confidence (a measure of spread) and the incidence of over (and under) estimation. I find that the future component of intertemporal utilities dominates schooling decisions. I find a strong incidence of under-estimation among the more able and a much smaller incidence of over-estimation among the low ability group. At the medium ability spectrum, there is evidence of some over-estimation. The degree of confidence is high and implies that agents have a substantial amount of inside information (36% of the population act on a degenerate subjective distribution). Overall, the variance of the objective ability heterogeneity distribution is 4 times as large the variance of the distribution characterizing subjective beliefs.
urn:nbn:de:101:1-20080401109
Keywords: 330; Bildungsverhalten; Erwartungstheorie; Persönlichkeitspsychologie; Bildungsökonomik; Italien